2016
DOI: 10.1111/pcmr.12487
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the Cdon gene potentiates congenital nevus development mediated by NRASQ61K

Abstract: Summary Congenital nevi develop before birth and sometimes cover large areas of the body. They are presumed to arise from the acquisition of a gene mutation in an embryonic melanocyte that becomes trapped in the dermis during development. Mice bearing the Cdk4R24C::Tyr‐NRASQ61K transgenes develop congenital nevus‐like lesions by post‐natal day 10, from melanocytes escaping the confines of hair follicles. We interbred these mice with the collaborative cross (CC), a resource that enables identification of modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Using a screen tool to detect natural genetic variation that modifies the density and histopathology of melanocytic nevi developing in a melanoma-prone mouse model, we found that nevus development was exacerbated in a cellextrinsic manner by keratinocytes. It involves up-regulation of Shh signaling and its downstream targets such as Gli transcription factors in keratinocytes and their subsequent secretion of the melanocyte mitogen Edn1 (Chitsazan et al, 2016(Chitsazan et al, , 2018. It is well known that nevi mostly carry cell intrinsic oncogenic mutations (e.g., BRAF, NRAS, GNAQ) that stimulate the MAPK pathway, but little is known about germline factors playing a role in nevus growth.…”
Section: Introductionmentioning
confidence: 99%
“…Using a screen tool to detect natural genetic variation that modifies the density and histopathology of melanocytic nevi developing in a melanoma-prone mouse model, we found that nevus development was exacerbated in a cellextrinsic manner by keratinocytes. It involves up-regulation of Shh signaling and its downstream targets such as Gli transcription factors in keratinocytes and their subsequent secretion of the melanocyte mitogen Edn1 (Chitsazan et al, 2016(Chitsazan et al, , 2018. It is well known that nevi mostly carry cell intrinsic oncogenic mutations (e.g., BRAF, NRAS, GNAQ) that stimulate the MAPK pathway, but little is known about germline factors playing a role in nevus growth.…”
Section: Introductionmentioning
confidence: 99%
“…Cdk4::NRAS mice develop dermal nevi by postnatal day 10 (P10), from melanocytes escaping the hair follicles (Chitsazan et al, 2016). Cdk4 R24C/R24C ::Tyr-NRAS Q61K/þ males were bred with females from many CC strains to generate progeny heterozygous for Cdk4 and NRAS transgenes.…”
Section: Genetic Background Dictates the Histopathology Of Melanocytimentioning
confidence: 99%
“…Many transgenic mice carrying melanocyte-specific oncogenic mutations develop dermal melanocytic proliferations reminiscent of giant congenital nevi (Pawlikowski et al, 2013;Shakhova et al, 2012). Transgenic Cdk4 R24C ::Tyr-NRAS Q61K (hereafter termed Cdk4::NRAS) mice begin to develop dermal nevi during the second week after birth (Chai et al, 2014;Chitsazan et al, 2016). Because the corresponding developmental period in which embryonic melanocytes have mostly migrated to the hair bulb is prenatal in humans, beginning at around 18 weeks (Gleason et al, 2008), and the examination of aborted foetuses at this stage has indicated the presence of deep dermal nevi at this stage (Cramer and Fesyuk, 2012), one might expect that the mechanisms promoting escape of melanocytes from the hair follicle to the dermis should be similar in both species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CC panel – and indeed any recombinant inbred panel – can further be used by intercrossing CC lines (Graham et al, 2015; Rasmussen et al, 2014) or crossing CC lines to an inbred strain with a genetic variant of interest to identify modifiers of the variant (Chitsazan et al, 2016). …”
Section: Mapping Neurobehavioural Traits In Moderately To Highly Recomentioning
confidence: 99%